2015
DOI: 10.1108/cdi-11-2014-0152
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of perceived overqualification: a three-wave study

Abstract: Purpose – The purpose of this paper is to investigate the role of job search on perceived overqualification by applying the theory of planned behavior and including financial need and openness to experience as moderators. Design/methodology/approach – Three questionnaires were given at weeks 1, 8 and 12 to 436 practice firm participants. A total of 119 completed all three questionnaires. The authors used partial least squares to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Akkermans, Brenninkmeijer, Huibers and Blonk, 2013;Plomp et al, 2016), and self-efficacy (e.g. Guerrero and Hatala, 2015;Lee and Park, 2012). Also, themes such as planned happenstance (e.g.…”
Section: Trending Topic #6: Career Capitalmentioning
confidence: 99%
“…Akkermans, Brenninkmeijer, Huibers and Blonk, 2013;Plomp et al, 2016), and self-efficacy (e.g. Guerrero and Hatala, 2015;Lee and Park, 2012). Also, themes such as planned happenstance (e.g.…”
Section: Trending Topic #6: Career Capitalmentioning
confidence: 99%
“…To date, research exploring moderators of the POQ–external job searching relationship has focused only on factors related to individual needs and values (e.g., Guerrero & Hatala, 2015; Maynard & Parfyonova, 2013). By contrast, our model delineates how each opportunity (i.e., PEM) and motivation (i.e., proactive personality and PO fit) factor differentially shapes an overqualifier's job searching processes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, building upon our first point, the Harari et al (2017) meta‐analysis found that artifacts accounted for only 29.37% of the variance for the POQ–external job searching association, suggesting that moderators may well exist for this relationship (Hunter & Schmidt, 2004). Previous studies have mainly focused on how individual needs and values (e.g., financial need; Guerrero & Hatala, 2015; competence and growth work values; Maynard & Parfyonova, 2013) moderate the POQ–job searching behavior relationship, neglecting the roles of abilities, motivations, and opportunities to move or stay relevant for the overqualified individuals. This limited set of moderating variables is insufficient to fully explain the POQ–external/internal job searching association and invites continuous effort to explore other variables influencing these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This theory was validated by Xi et al 2017that job search selfefficacy was linked to employability. Similarly, self-efficacy for job search intentions and outcome expectations was shown to influence applicants job search planning and job search behaviours (Fort, Jacquet, & Leroy, 2011;Guerrero & Hatala, 2015). Job search behaviour selfefficacy is also linked to job search outcome self-efficacy (Kim, Kim, & Lee, 2019) and perceived employability (Atitsogbe, Mama, Sovet, Pari, & Rossier, 2019).…”
Section: Self-efficacymentioning
confidence: 94%